Regulation on the Position of the State Civil Apparatus in the General Sorting of Indonesia - Separen; Muhammad Zulhidayat; Sri Endang Kornita (Magister Ilmu Hukum Fakultas Hukum Universitas Riau, 2023)
This study examines the regulation of the position of the State Civil Apparatus (ASN) in the context of General Elections (Pemilu) in Indonesia. This research uses normative juridical method with qualitative descriptive analysis approach. Regulations on the position of civil servants are very clearly regulated in the legislation on how to regulate civil servants to be more optimal in supporting government activities to benefit the community as much as possible and be fair and always maintain neutrality in elections. Based on the results of the study, there are several regulations governing the position of civil servants in elections in Indonesia, namely the 1945 Constitution, the Civil Service Law, the Election Law, the Corps Life Government Regulation and the Civil Servant Code of Ethics, the Government Regulation on Civil Servant Discipline, and the Circular Letter of the Chairman of KASN concerning the Neutrality of Civil Servants.